2020
DOI: 10.3390/v12080839
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Regulation in Macrophages and Susceptibility to HIV-1

Abstract: Macrophages are the first line of defence against invading pathogens. They play a crucial role in immunity but also in regeneration and homeostasis. Their remarkable plasticity in their phenotypes and function provides them with the ability to quickly respond to environmental changes and infection. Recent work shows that macrophages undergo cell cycle transition from a G0/terminally differentiated state to a G1 state. This G0-to-G1 transition presents a window of opportunity for HIV-1 infection. Macrophages ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 126 publications
(169 reference statements)
0
25
0
Order By: Relevance
“…A peculiar property of macrophages is their long survival in culture in a nonproliferating state (whereas, in vivo, tissue-resident macrophages, TRM, undergo a slow homeostatic proliferation driven by cytokines secreted in an autocrine fashion in order to persist indefinitely in the host [ 4 , 5 ]) caused by a physiological arrest of their cell cycle. This aspect of their biology has been recently revisited for its relevance to HIV infection and the role of restriction factors, with particular regard to SAMHD1 (SAM domain and HD domain-containing protein 1), a hydrolase processing deoxynucleotides triphosphates (dNTPs) physiologically involved in DNA repair mechanisms [ 13 , 89 ]. SAMHD1 acts by depleting the pool of dNTPs, the “building blocks” necessary for the reverse transcription process to synthesize viral DNA before its integration into the host cell genome.…”
Section: Viral Proteins Counteracting Restriction Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…A peculiar property of macrophages is their long survival in culture in a nonproliferating state (whereas, in vivo, tissue-resident macrophages, TRM, undergo a slow homeostatic proliferation driven by cytokines secreted in an autocrine fashion in order to persist indefinitely in the host [ 4 , 5 ]) caused by a physiological arrest of their cell cycle. This aspect of their biology has been recently revisited for its relevance to HIV infection and the role of restriction factors, with particular regard to SAMHD1 (SAM domain and HD domain-containing protein 1), a hydrolase processing deoxynucleotides triphosphates (dNTPs) physiologically involved in DNA repair mechanisms [ 13 , 89 ]. SAMHD1 acts by depleting the pool of dNTPs, the “building blocks” necessary for the reverse transcription process to synthesize viral DNA before its integration into the host cell genome.…”
Section: Viral Proteins Counteracting Restriction Factorsmentioning
confidence: 99%
“…As HIV-1 is devoid of Vpx, it has been highly debated whether a similar mechanism would be carried out by other accessory viral proteins. In this regard, Ferreira and colleagues have reported that, although in the absence of cell division [ 13 ], macrophages in the G 0 phase express p21/Waf1 (previously shown to represent a negative regulator of virus replication in macrophages [ 51 ]) together with high levels of SAMHD1, thereby resulting in a highly restricted state for virus replication. A switch to G 1 has been associated with the downregulation of p21/Waf1, increased expression of cyclin-dependent kinase 1 (CDK1) and inactivation of SAMHD1 by phosphorylation, leading to increased dNTP levels and the unleashing of virus replication.…”
Section: Viral Proteins Counteracting Restriction Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CD4 + T cells are the primary targets of HIV, myeloid cells such as monocytes and macrophages are infected by R5 tropic and dual tropic strains of HIV and have unique properties that could lead to persistent HIV infection even in the presence of active retroviral therapy (ART) 1, 2 . For instance, macrophages have distinct and malleable metabolic properties compared to T cells that make them intrinsically resistance to HIV-induced cytopathic effects and less susceptible to some antiretroviral drugs 3, 4 . These properties include, but are not limited to, innate immunity pathways that involve viral nucleic acid lethal mutation by enzymatic cytidine deamination 5, 6 , dramatically reduced dNTP pools and composition through the action of SAMHD1 dNTPase 7, 8 , and the ability to transiently access G0 and G1 stages of the cell cycle 4, 9, 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the mechanism of action of this dendrimer against HIV-1 both in vitro and in vivo, we studied the possibility that our G2-S16 dendrimer was able to inhibit the HIV-1 within macrophages. Macrophages play a major role as potential viral reservoirs, not only because they appear to have greater resistance to cytopathic effects than T cells [10,11], but they also are capable of containing competent viruses for weeks in lymphoid organs, preventing the interaction of ART. Thus, during the acute phase of HIV-1 infection, macrophages establish primary infection but perivascular macrophages deliver the virus to different organs, including the brain [12,13], establishing itself as an immune sanctuary [14].…”
Section: Introductionmentioning
confidence: 99%